Kepemimpinan Kepala Madrasah dalam Pelaksanaan Manajemen Berbasis Madrasah di MTsN 1 Kota Bima Tahun Ajaran 2020-2021 - M. Adnan (Lembaga Bale Literasi, 2023)
The role of principle or leadership in madrasah is a very important element in the implementation of Madrasah-Based Management in the form of stages that must be taken in achieving the goals of Lil Alamin Rahmatan Islamic Education, so that it can be said that the curriculum is a major component of Islamic education, which is organized and presented scientifically and psychologically for educational goals at the level of Madrasah Tsanawiyah or Junior High School to foster a sense of tolerance, mutual respect, mutual trust, and mutual need. This study aims to obtain data on Madrasah Based Management, the principle of Madrasah Leadership, the relevance of the curriculum of the MTsN 1 Kota Bima academic year 2020-2021. This research was conducted using field studies. Data collection is done by observation, interviews, and documentation to get information about the problem under study. While the data analysis is conducted to provide a description and draw conclusions from it. Based on the above analysis, it can be concluded that the results of the study show that the role of Madrasah principle Leadership in implementating Madrasah-Based Management at MTsN 1 Kota Bima Cirebon is through process of discussion, modeling, and habituation.